Gut Microbiota Profile in Adult Patients with Idiopathic Nephrotic Syndrome. (19th February 2021) - He, Hanchang; Lin, Minwa; You, Lu; Chen, Tongqing; Liang, Zijie; Li, Dao; Xie, Chao; Xiao, Guanqing; Ye, Peiyi; Kong, Yaozhong; Zhou, Youlian
Abstract : Background . Increasing evidences have reported gut microbiota dysbiosis in many diseases, including chronic kidney disease and pediatric idiopathic nephrotic syndrome (INS). There is lack evidence of intestinal microbiota dysbiosis in adults with INS, however. Here, we to address the association between the gut microbiome and INS. Methods . Stool samples of 35 adult INS patients and 35 healthy volunteers were collected. Total bacterial DNA was extracted, and the V4 regions of the bacterial 16S ribosomal RNA gene were sequenced. The fecal microbiome was analyzed using bioinformatics. The correlation analysis between altered taxa and clinical parameters was also included. Results . We found that microbial diversity in the gut was reduced in adult patients with INS. Acidobacteria, Negativicutes, Selenomonadales, Veillonellaceae, Clostridiaceae, Dialister, Rombousia, Ruminiclostridium, Lachnospira, Alloprevotella, Clostridium sensu stricto, Megamonas, and Phascolarctobacterium were significantly reduced, while Pasteurellales, Parabacteroides, Bilophila, Enterococcus, Eubacterium ventriosum, and Lachnoclostridium were markedly increased in patients with INS. In addition, Burkholderiales, Alcaligenaceae, and Barnesiella were negatively correlated with serum creatinine. Blood urea nitrogen levels were positively correlated with Christensenellaceae, Bacteroidales_S24.7, Ruminococcaceae, Ruminococcus, and Lachnospiraceae_NK4A136, but were negatively correlated with Flavonifractor_plautii and Erysipelatoclostridium_ramosum . Enterobacteriales, Enterobacteriaceae, Porphyromonadaceae, Escherichia/Shigella, Parabacteroides, and Escherichia_coli were positively correlated with albumin. Proteinuria was positively correlated with Verrucomicrobia, Coriobacteriia, Thermoleophilia, Ignavibacteria, Coriobacteriales, Nitrosomonadales, Coriobacteriaceae, and Blautia, but was negatively correlated with Betaproteobacteria, Burkholderiales, and Alcaligenacea e. Conclusion . Our findings show compositional alterations of intestinal microbiota in adult patients with INS and correlations between significantly altered taxa and clinical parameters, which points out the direction for the development of new diagnostics and therapeutic approaches targeted intestinal microbiota.